Histomorphology of the Subregions of the Scapholunate Interosseous Ligament and Its Enthesis - Liew, Mei Yen; Mortimer, Jeremy W.; Paxton, Jennifer Z.; Tham, Stephen; Rust, Philippa A. (Journal of Wrist Surgery, 2021)
Background The scapholunate interosseous ligament (SLIL) has three subregions: dorsal, proximal, and volar. The SLIL enthesis has not previously been studied despite its important mechanical function in wrist joint biomechanics.Questions/Purposes This study aims to compare the histomorphological differences between the SLIL subregions, including at their entheses. Three questions are explored: Do the gross dimensions differ between SLIL subregions? Does the enthesis qualitatively, and its calcified fibrocartilage (CF) quantitatively, differ between (a) SLIL subregions and (b) scaphoid and lunate attachments?Methods Twelve fresh-frozen human cadaveric wrists were dissected and the gross dimensions of the SLIL subregions measured. Subregions were histologically processed for morphological and compositional analyses, including quantification of enthesis CF area.Results The dorsal subregion was the thickest. The dorsal and volar subregions had fibrocartilaginous entheses, while the proximal subregion was attached to articular cartilage. The dorsal subregion had significantly more CF than the volar subregion. There was no significant difference in the enthesis CF between scaphoid and lunate attachments in the three subregions.Conclusions There are significant morphological differences between the SLIL subregions. The dorsal subregion has the largest amount of CF, which is consistent with the greater biomechanical force subjected to this subregion. The similar histomorphology of the ligament at the scaphoid and lunate entheses suggests that similar biomechanical forces are applied to both attachments.Clinical Relevance The histomorphological results confirm that the dorsal subregion is the strongest of the three subregions. The results from the entheseal region may have important implications in the study of graft incorporation during SLIL reconstruction.
Keywords: scapholunate; ligament; enthesis; morphology; histology